Réponses

Meilleure réponse !
2014-02-04T12:51:11+01:00
Développement
(3x-5)² -2(3x-5)
9x² -30x +25 -6x +10
9x² -36x +35
Factorisation
(3x-5)(3x-5) -2(3x-5)
(3x-5) (3x-5 -2)
(3x-5)(3x-7)
E = pour x = -2
(3x-5)(3x-7)
(3 X -2 -5)(3X -2 -7)
(-6 -5)(-6 -7)
(-11)(-13)
+143
Equation(3x-5)(3x-7)=0
3x = 5
x = 5/3
3x=7
x = 7/3
2014-02-04T13:02:25+01:00
1)
E= 3x-5)² -2(3x-5)
= 9x² -30x +25 -6x +10
= 9x² -36x +35

2)
E= (3x-5 ) (3x-5) -2 (3x-5)
=(3x -5) ( 3x-5 -2)
=(3x-5 ) (3x-7)

3)
E = pour x = -2

E= (3x-5) (3x-7)
= (3x -2 -5) (3x - 2 -7)
= (-6 -5)(-6 -7)
= -11×(-13)
= 143

4)
(3x -5) ( 3x-7 ) = 0
3x = 5
x =  5/3
3x = 7
x = 7/3